Modeling Appropriate Fiscal Targets and Optimal Consolidation Paths for Resource-Rich Countries : The Case of Suriname - Kanda, Daniel (IMF Working Papers; Working Paper ;, 2014)
This paper first attempts to quantify the natural resource wealth of Suriname from the perspective of its impact on the fiscal position, and then assesses the fiscal sustainability gap in that context. It then presents models to address the question of the optimal path of fiscal consolidation given the outlook for natural resource wealth, macroeconomic conditions, and country authority preferences.